When the moon turns to blood eaudiobook Lori vallow, chad daybell, and a story of murder, wild faith, and end times. - Sottile, Leah (2022)
Inspired by Jon Krakauer's Under the Banner of Heaven and Jess Walter's Every Knee Shall Bow , WHEN THE MOON TURNS TO BLOOD explores modern-day survivalism and end-times extremism through the story of Lori Vallow and her husband, grave digger turned doomsday novelist, Chad Daybell. When police in Rexburg, Idaho perform a wellness check on seven J.J. Vallow and his sister, sixteen-year-old Tylee Ryan, both children are nowhere to be found. Their mother, Lori Vallow, gives a phony explanation, and when officers return the following day with a search warrant, she, too, is gone. As the police begin to close in, a larger web of mystery, murder, fanaticism and deceit begins to unravel. Vallow's case is sinuously complex. As investigators prod further, they find the accused Black Widow has an unusual number of bodies piling up around her. WHEN THE MOON TURNS TO BLOOD tells a gripping story of extreme beliefs, snake oil prophets, and explores the question: if it feels like the world is ending, how are people supposed to act?